Early Historic Material Culture in Karnataka with Particular Reference to Banavasi, North Kanara, India. (22nd February 2017) - Thakur, Hema
In this paper I have tried to reconstruct the pattern of development at the early historic settlement of Banavasi, Karnataka. Karnataka has been broadly divided between forested Malnad and Maidan which is relatively more open and flat. The settlement of Banavasi lies in Malnad. Malnad has good drainage and enjoys cool climatic conditions. It is well-known for the cultivation of cash crops such as cashew, pepper, cardamom and cinnamon. Cool climate and heavy rains have resulted in a thick forest cover. Forests have given valuable products such as Teak, Ebony, Bamboo, Sandalwood, etc. Further, Malnad enjoys the benefit of having metals and minerals. The author has tried to explain that favourable climate and natural resources were the major factors responsible for rich habitation and over-all prosperity. This prosperity was manifested by rich archaeological assemblage that included structures, pottery, beads, terracottas, sculptures, coins, inscriptions, etc. The aim of this paper has been to have a comprehensive understanding of the socio-political and economic development and to contextualize it in relation to the local geographical setting. The main engagement has been with the basic issues concerning subsistence of the settlement, the early beginnings of social stratification and ruling authority and the contemporary religious beliefs. The principal concern of the author is to understand the patterns about human lifeways as indicated by the material remains of the period.